Integrated and Personalised Risk Management in the Sensing Enterprise - Lázaro, Óscar; Moyano, Agustín; Uriarte, Mikel; González, Alicia; Meneu, Teresa; Fernández-Llatas, Juan Carlos; Traver, Vicente; Molina, Benjamín; Palau, Carlos; López, Óscar; Sánchez, Etxahun; Ros, Saioa; et al. (IntechOpen, 2012)
None